OPPORTUNITIES OF CONTACT LITHOLYSIS IN THE TREATMENT OF GALLSTONE DISEASE - Ye. V. Razmakhnin; S. L. Lobanov; O. G. Konovalova (Бюллетень сибирской медицины, 2014)
For the treatment of calculouscholecystitis in patients with high-risk surgery in the treatment of choledocholithiasis in an effort to preserve the sphincter apparatus major duodenal papilla are encouraged to use the contact litholysis gallstones saxifragant mixture of octanoic acid – glycerol in a ratio of 1 : 1.The possibility of dissolution of stones in experiments in vitro (n = 51) and in vivo (n = 35), confirmed the low toxicity and high efficiency of the proposed technique. In vitro experiments, for more convenient evaluation was introduced conditional coefficient (K) that reflects the time lithodialysis in minutes per 1 mg of the stone weight. In experiments in vitro: K' = 5.76 (n = 51). It is noted that in the group of stones with low mineralization using saxifragant mixture K' = 4.50 (n = 15), with an average K' = 5.76 (n = 17), high K' = 6.88 (n = 19).In an in vivo experiment used 35 sexually mature rabbits after modeling cholelithiasischolecystitis was made through the introduction of a mixture of saxifragant rate of 0.2 ml/kg body weight once a day. Lowmineralized stones disappeared in all cases (after the double administration) medium mineralizedwhen administered for 3 days or more, the highly mineralized 4 – day of treatment. After treatment, histologically and biochemically, were found pronounced toxic effects of the drug.The clinic is possible to impose mikroholetsistostomy under ultrasound gui dance, irrigation lumen of the gall bladder, treatment of acute inflammation, followed by solvent solubility and control of stones with ultrasound studies, or using fistuloholangiografiyu. When choledocholithiasis, especially when residual common bile duct stones in an effort to preserve the sphincter apparatus ma jor duodenal papilla, possibly through the introduction of a mixture of saxifragant hepaticocholedochus established percutaneously transhepatic under ultrasound guidance, either through drainage nazobi liarny established endoscopically through major duodenal papilla. The advantages of this method compared to peers is less toxic solvent, speed lysing effect, the efficiency of the process calculi with different composition (cholesterol and pigment). Compared with the traditional methods of trea tment of gallstone disease differs minimally invasive and thus significantly reduces the risk of intra -and postoperative complications, both local and general, and significantly shorten the treatment of patients and their stay in hospital.